The Kurdish Position on Political and Military Transformations in Iraq (1979-1980) - Wadi Muhammad Al-Saadoun, Assist. Lect. Noura; Abdul Reda Aylan Al-Khafaji, Prof. Dr. Rafid (Basra studies journal, 2024)
This research titled "The Kurdish Position on Political and Military Transformations in Iraq (1979-1980)" aims to investigate a crucial aspect of contemporary Iraqi history. It examines how the Kurds responded to political changes during this period, initially aligning with new authorities presenting themselves as defenders of Kurdish interests. However, this alignment shifted dramatically with the outbreak of the Iran-Iraq war, leading to joint military operations between the Iranian army and Kurdish factions controlling significant parts of Iraqi Kurdistan. The study concludes that Kurdish political dynamics underwent a profound transformation during this era. The central government’s altered approach marked a departure from traditional Kurdish grievances. Consequently, political and military shifts allowed Kurds to leverage the Kurdish question as a focal point of contention with the central government, particularly amidst the Iran-Iraq conflict over control of Kurdistan.